Solutions to Power Quality Problems in Electric Vehicle Battery Recharging - Julianus Gesuri Daud; Deitje Sofie Pongoh; Samsu Tuwongkesong; Muchdar Dg. Patabo (Poltanesa, 2025)
The recent proliferation of electric vehicle (EV) charging stations has a serious impact on the power quality of the electricity distribution network. This issue cannot be ignored, as EV chargers are a type of non-linear load. With the increasing presence of non-linear loads in modern power systems due to the influence of EV charging, harmonic distortion, both THD and TDD, will become a significant problem, especially for distribution transformers that supply power to EVs. The increasing number of high-power electric vehicle batteries being charged at DC fast-charging stations, especially those with large load capacities, and when parallel with other vehicles, can cause overloads during peak hours, sudden power gaps, and voltage drops, all of which contribute to power quality issues, particularly in the surrounding electricity grid. Harmonic distortion, particularly due to the access of EV power supplies to the distribution network, which causes increased power quality disturbances, must be eliminated because the resulting odd harmonics will impact the performance of electrical equipment due to the suboptimal P and Q power in the distribution line. To understand the impact of charging electric vehicles, high-efficiency chargers are required in the power grid. Simulations revealed a high harmonic spectrum approaching 25%, but this was reduced to a much lower and safer level using passive filters.